Venous thromboembolism after delayed surgery for a hip fracture: A retrospective cohort study. Issue 12 (15th October 2020) - Yoon, Jae Youn; Kim, Shinseok; Chang, Jae Suk; Yoon, Pil Whan; Kim, Ji Wan
Abstract : Aim: The purpose of this study was to investigate the demographic characteristics and prevalence of postoperative venous thromboembolism (VTE) in delayed hip fracture patients referred to our hospital (a tertiary referral center), and further verify the effect of intensive prophylaxis protocol in preventing the occurrence of VTE. Methods: We retrospectively evaluated 264 hip fracture patients whose surgery was delayed by >24 h. The patients were divided into two groups, according to the VTE prophylaxis protocol (conventional vs intensive). We evaluated the time from injury to surgery, and analyzed the prevalence of postoperative symptomatic VTE between the groups. The patient outcome measures, including in‐hospital mortality and 30‐day‐mortality after hip surgery, were also evaluated. Results: The mean time from injury to operation was 127.4 h (95% confidence interval 92.2–162.7 h). The incidence of postoperative symptomatic VTE was 5.9% in the conventional prophylaxis group and 0.8% in the intensive prophylaxis group. The intensive prophylaxis group had a significantly lower incidence of postoperative VTE ( P = 0.036). Eight patients with deep vein thrombosis on preoperative screening who underwent inferior vena cava filter insertion did not develop postoperative symptomatic VTE. Logistic regression analysis results also showed that the protocol statistically reduced the development of VTE (odds ratio 0.14, 95% CI 0.02–1.21, P = 0.042). Conclusions: Delayed hip fracture surgery resulted in a higher incidence of VTE in patients who received conventional prophylaxis; however, our intensive prophylaxis protocol successfully prevented postoperative symptomatic VTE, including pulmonary embolism. Geriatr Gerontol Int 2020; 20: 1151–1156 .